The Poole Iron Age logboat - Berry, Jessica,; Parham, David,; Appleby, C. A. (Archaeopress Publishing Ltd, 2019)
This text is the culmination of significant multi-disciplinary work carried out by a variety of specialists, from conservators to woodworking and boatbuilding experts, exploring the history of the Poole Iron Age logboat (today imposingly displayed in the entrance to Poole Museum in Dorset) and also its functionality - or lack of - as a vessel.